2006
DOI: 10.1287/opre.1060.0281
|View full text |Cite
|
Sign up to set email alerts
|

On the Asymptotic Validity of Fully Sequential Selection Procedures for Steady-State Simulation

Abstract: We present fully sequential procedures for steady-state simulation that are designed to select the best of a finite number of simulated systems when "best" is defined by the largest or smallest long-run average performance. We also provide a framework for establishing the asymptotic validity of such procedures and prove the validity of our procedures. An example based on the M/M/1 queue is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…We do not review this literature in detail, but state only that an overview may be found in [1] and that a more recent policy which performs quite well in the multistage setting with normal rewards is given in [23], [22]. Other sequential and staged policies for independent normal rewards with frequentist guarantees include those in [25], [27], [17], [26], and [24].…”
Section: Introductionmentioning
confidence: 99%
“…We do not review this literature in detail, but state only that an overview may be found in [1] and that a more recent policy which performs quite well in the multistage setting with normal rewards is given in [23], [22]. Other sequential and staged policies for independent normal rewards with frequentist guarantees include those in [25], [27], [17], [26], and [24].…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Nelson (2006) justify this asymptotically in a diffusion-approximation framework when certain technical conditions, such as those for a functional central limit theorem, are valid. We presume that such technical conditions hold in this subsection.…”
Section: D1 Autocorrelated Outputmentioning
confidence: 98%
“…This assumption often holds in many applications where the simulation estimate itself is the average of a large number of observations generated during the simulation process. There are also procedures that are also asymptotically valid when simulation samples are non-normal (Kim and Nelson, 2006). Subset selection procedures relax the objective of selecting the best to selecting a subset that contains the best solution .…”
Section: Ranking and Selectionmentioning
confidence: 99%